Clinical and epidemiological characteristics of meningococcal infection morbidity in Penza Region for the period 2007-2019 - V. L. Melnikov; N. N. Mitrofanova; A. E. Mitushkin (Журнал инфектологии, 2021)
Objective. To study the clinical and epidemiological characteristics of meningococcal disease morbidity in the Penza Region population for the period 2007-2019.Materials and methods. The retrospective analysis carried out of archival documents of a specialized infectious diseases hospital in Penza and materials of the center of the Federal Service for Supervision of Consumer Rights Protection and Human Well-being. Methods of statistical processing were used for the analysis.Results and discussion. As a result of the analysis, it was revealed that the incidence of meningococcal infection in the Penza region exceeds the average level in Russia for almost the entire time period under study. We revealed the predominance of the share of the child population in the structure of total morbidity throughout the entire time tranche under study was revealed. The presence of 4 peaks in the mortality rate was found — in 2009, 2012, 2014 and 2016. On the territory of the Penza region, the infection has a pronounced winter-spring seasonality, there are generalized forms of meningococcal infection and localized forms of meningococcal infection.Conclusions. Thus, meningococci of serogroups B and C prevail in the serogroup landscape of meningococci in the Penza region. The excess of the average Russian indicators of the incidence of meningococcal infection was revealed by 2 or more times throughout the entire study period. patients under the age of 14 from unorganized groups predominate among patients with meningococcal infection. the Gender structure is dominated by males from rural areas. The infection has a pronounced winter-spring seasonality. The most common clinical forms are meningitis and mixed form.